What is a cognitive ontology, anyway?. (4th May 2017) - Janssen, Annelli; Klein, Colin; Slors, Marc
Abstract : This special issue brings together philosophical perspectives on the debate over cognitive ontology. We contextualize the papers in this issue by considering several different senses of the term "cognitive ontology" and linking those debates to traditional debates in philosophy of mind.